Effect of Nitrate on the Performance of a Single-Chamber Microbial Fuel Cell Equipped With a Titanium Based Lead-dioxide Cathode - Chen, Shaohua; Wang, Jiaquan; Xia, Xuelan; Yang, Jinping; Chen, Chen; Lu, Fei (Asian Journal of Chemistry, 2012)
The biodegradation of nitrate in the wastewater was studied when using a single-chamber microbial fuel cell (SMFC) equipped with a titanium based lead-dioxide cathode. The results showed that the cell could readily degrade the nitrate, but high concentration nitrate would affect the electricity production of the cell. After raising the COD concentration in the singlechamber microbial fuel cell, the cell got good unity in dentrification and electricity production. Two different nitrate-treating methods(static and continuously feed system) were investigated respectively on the single-chamber microbial fuel cell's performance. The results demonstrated that the continuously feed system was better in both the electricity production and dentrification than the static system, which indicated the continuously feed system would more satisfy the need of practial application in denitrification treatment.